Mathematical Methods and Models in Economic Planning, Management and Budgeting - Mutanov, Galimkair (Springer, 2015)
This book describes a system of mathematical models and methods that can be used to analyze real economic and managerial decisions and to improve their effectiveness. Application areas include: management of development and operation budgets, assessment and management of economic systems using an energy entropy approach, equation of exchange rates and forecasting foreign exchange operations, evaluation of innovative projects, monitoring of governmental programs, risk management of investment processes, decisions on the allocation of resources, and identification of competitive industrial clusters. The proposed methods and models were tested on the example of Kazakhstan’s economy, but the generated solutions will be useful for applications at other levels and in other countries.